PERAN DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN KELUARGA BERENCANA DALAM MENCEGAH PERNIKAHAN USIA DINI DI KOTA SERANG - Ripadli; Febrian Alwan Bahrudin; Wika Hardika Legiani (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
Abstract   This research addressed the issue of early marriage, which remains a frequent occurrence in Serang City, highlighting the need for effective prevention efforts. The purpose of this study is to assess the role of the Department of Women Empowerment, Child Protection, and Family Planning (DP3AKB) in preventing early marriage in Serang City. This study employs a qualitative method with a descriptive approach. Data were gathered through interviews, observations, and documentation to provide clear and detailed insights into the phenomena or facts observed in the field. The findings of this study reveal that the prevalence of early-age marriages in Serang City remains considerably high, with a total of 21 couples officially registered in 2024. As a regulatory body, the DP3AKB of Serang City plays a crucial role in shaping policies through the enactment of regional regulations and actively engages in coordination and collaboration with various relevant stakeholders. As a catalyst, the DP3AKB of Serang City has delivered guidance through the Communication, Information, and Education program targeting the community, particularly parents and children. Furthermore, in its role as a facilitator, the DP3AKB of Serang City provides free consultation services through the Family Learning Center (PUSPAGA) program. Therefore, this role is anticipated to be increasingly proactive and sustainable in mitigating the incidence of early marriage in Serang City through comprehensive programs, educational initiatives, and the reinforcement of cross-sectoral collaboration.   Keywords: Early Marriage, The Role of Government